Shrinking spaces in Israel: Contraction of democratic space, consolidation of occupation, and ongoing human rights violations call for a pradigm shift in Europe's policies - Muriel Asseburg (Stiftung Wissenschaft und Politik (SWP), 2017)
Israel has always claimed to be the only democracy in the Middle East. Yet the current government coalition is dominated by right-wing, ultra-Orthodox and national-religious parties advocating illiberal policies and seeking Jewish dominance across 'Eretz Israel' - Israel itself and the occupied Palestinian territories. Accordingly, the government is working firstly to emphasise the Jewish elements in Israel's identity. It is secondly pushing ahead with settlement-building in and de facto annexation of parts of the occupied territories. Thirdly, it is steadily shrinking the spaces for Israel's civil society and human rights organisations. Germany and the EU should press Israel to comply with international law, improve the human rights situation and preserve spaces for civil society to thrive. In their policies, working towards respect for human rights and international law should no longer come second to conflict resolution.
Keywords: 320